Redesigning a 300 ft Barge as a Floating Hotel to Support Tourism in the Thousand Islands - Augustinus Pusaka; Erwin Gunawan; Fanny Octaviani (International Journal of Marine Engineering Innovation and Research, 2023)
The Thousand Islands is a marine tourism area located around Jakarta, which has several beautiful and charming islands. Many cargo barge decks are not operating because natural resources are starting to decline. One of the innovations to increase tourist attraction is by designing a floating hotel using a 300 ft barge as a supporting facility in the Thousand Islands. Determination of the main size of the ship using the method of comparison of several barge sizes of 300 ft and stability calculations using the A.N-Krylov method with maxsurf software. Obtained ship size LOA = 91.5 m, B = 27.5 m, H = 5.5 m, T = 4.3 m. The superstructure modification has three decks, each deck being 3 m high with a different length. The results of the floating hotel design have a total of 52 rooms that can accommodate 116 visitors. There are superior room types, deluxe rooms and suite rooms and are equipped with other facilities. The floating hotel's safety equipment includes 8 lifebuoys, 188 lifejackets, 4 lifeboats and 8 liferafts. The stability of the floating hotel meets the intact stability criteria of the IMO standard A.749(18) Ch3 - Design criteria applicable to all ships.